An Empirical Study on Cybersecurity Awareness, Cybersecurity Concern, and Vulnerability to Cyber-attacks - Mittal, Chahak (International Journal of Scientific Research and Management (IJSRM), 2024)
The research aimed to delve into the landscape of cybersecurity awareness and concern levels within Punjab, India, shedding light on the specific demographic groups most susceptible to cyber-attacks. Through meticulous survey administration and data analysis, the study pinpointed a noteworthy vulnerability: young adult females aged 18 to 29 residing in rural Punjab, particularly those either engaged in student pursuits or currently unemployed. This demographic emerged as disproportionately prone to cyber threats.Highlighting the gravity of this finding, the research underscores the urgency for tailored interventions to fortify the cyber defenses of this vulnerable population segment. A crucial facet of this approach involves the development of a prototype aimed at augmenting cybersecurity awareness and fostering ethical online conduct among the identified demographic. This prototype seeks to serve as a platform for delivering enhanced training modules tailored to the unique needs and challenges faced by young females in rural Punjab.Moreover, the paper delineates a comprehensive roadmap for the implementation and evaluation of these recommendations. Central to this plan is the deployment of an application based on the proposed prototype, designed to facilitate the delivery of targeted cybersecurity education and gauge its efficacy in bolstering cyber resilience among the identified demographic.This research not only illuminates the cybersecurity landscape in Punjab but also charts a proactive course of action aimed at mitigating vulnerabilities and empowering at-risk populations through informed intervention strategies. Through ongoing data collection and evaluation efforts, the efficacy of these interventions will be rigorously assessed, driving iterative refinement and optimization of cybersecurity initiatives tailored to the unique needs of Punjab's populace.